Implementasi Sistem Informasi Pengelolaan Surat Berbasis Web dengan Metode Rational Unified Process pada Politeknik - Yuliana Yuliana; Nur Idil Fitri Idris; Muhammad Nur Arbi; Raden Wirawan (Journal of Information System Research (JOSH), 2026)
Management of incoming and outgoing mail at Indotec Kendari Polytechnic is still done manually through recording in an agenda book, so the archive search process is less efficient, risks causing loss or damage to documents, and slows down the preparation of administrative reports. This study aims to implement a web-based mail management information system to improve the efficiency of the process of recording, storing, searching, and reporting letters. The system development method used is the Rational Unified Process (RUP) which consists of the stages of inception, elaboration, construction, and transition. The system was developed web-based using the PHP programming language and MySQL database, then tested using the Black Box Testing method to evaluate the suitability of the system functions with user needs. The test results show that all main functions of the system, including user authentication, incoming mail management, outgoing mail management, archive search, document upload, and report preparation, run according to functional requirements with a test success rate of 100%. The system implementation is able to improve the effectiveness of mail archive management, speed up the document search process, and simplify the preparation of administrative reports. The contribution of this research is to produce a web-based mail management information system developed using the Rational Unified Process approach, thus serving as an alternative digital solution to support the transformation of mail administration in higher education environments.